2012
DOI: 10.4049/jimmunol.1103269
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Protein 90-Mediated Peptide-Selective Presentation of Cytosolic Tumor Antigen for Direct Recognition of Tumors by CD4+ T Cells

Abstract: Tumor Ag-specific CD4+ T cells play important functions in tumor immunosurveillance, and in certain cases they can directly recognize HLA class II-expressing tumor cells. However, the underlying mechanism of intracellular Ag presentation to CD4+ T cells by tumor cells has not yet been well characterized. We analyzed two naturally occurring human CD4+ T cell lines specific for different peptides from cytosolic tumor Ag NY-ESO-1. Whereas both lines had the same HLA restriction and a similar ability to recognize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 45 publications
1
32
0
Order By: Relevance
“…Indeed, as part of the classical endogenous pathway of antigen presentation, data from in vitro studies suggested that HSP90 may be required for the binding and delivery of chaperoned, antigenic peptides with MHC I molecules to the cell surface (29). More recently, it has been shown that HSP90 can also facilitate direct tumor recognition by CD4 þ T cells via a nonclassical, MHC IImediated mechanism for presentation of intracellular tumor antigens (30). HSP90 also plays pivotal roles in efficient antigen cross-presentation and priming by antigen donor cells (31,32), and in both the functional and phenotypic regulation of T lymphocytes (33).…”
Section: The Hsp90 Paradox For Modulating Tumor Immune Responsesmentioning
confidence: 99%
“…Indeed, as part of the classical endogenous pathway of antigen presentation, data from in vitro studies suggested that HSP90 may be required for the binding and delivery of chaperoned, antigenic peptides with MHC I molecules to the cell surface (29). More recently, it has been shown that HSP90 can also facilitate direct tumor recognition by CD4 þ T cells via a nonclassical, MHC IImediated mechanism for presentation of intracellular tumor antigens (30). HSP90 also plays pivotal roles in efficient antigen cross-presentation and priming by antigen donor cells (31,32), and in both the functional and phenotypic regulation of T lymphocytes (33).…”
Section: The Hsp90 Paradox For Modulating Tumor Immune Responsesmentioning
confidence: 99%
“…Melanoma cells, APCs and keratinocytes may contribute to MHC class II-restricted presentation in melanoma tumors. Melanoma cells may express MHC class II and are capable of presenting endogenous membrane bound and cytoplasmic antigens on MHC class II [14, 15]. Melanoma tumor cells directly presenting antigen are capable of activating naïve T cells [12].…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned, targets of autoimmunity can be generated by chaperone-mediated autophagy [48] but endogenous processing has been reported for various autoantigens [6468] and tumor antigens [69•,70]. If, as in the case of influenza, the majority of MHC-II-restricted self-peptides are produced by endogenous processing, systems that restrict candidate autoantigens to endosomal processing may miss opportunities for mechanistic insights and therapeutic strategies.…”
Section: Resultsmentioning
confidence: 99%